Vegetation analysis, physico-chemical properties and economic potential of damar (Agathis dammara) in Mount Halimun Salak National Park,West Java, Indonesia - Yelin Adalina; RENY SAWITRI (Society for Indonesian Biodiversity, 2020)
Abstract. Adalina Y, Sawitri R. 2020. Vegetation analysis, physico-chemical properties and economic potential of damar (Agathis dammara) in Mount Halimun Salak National Park,West Java, Indonesia. Biodiversitas 21: 1122-1129. Analysing the potential of non-timber forest product (NTFP) plants in Mount Halimun Salak National Park (MHSNP) is one of the important aspects in supporting conservation and improving the economic status of communities around the forest. This study aims to determine the economic potential and benefits of damar plants (Agathis dammara) in MHSNP area of Kawah Ratu Resort, Sukabumi District, West Java, Indonesia along with analysis of damar plant forest and physico-chemical analysis of the copal/resin. The selection of research village was by purposive sampling and the selection of respondents was by random sampling. Forest vegetation in the Kawah Ratu Resort is entirely dominated by damar plants. The Important Value Index (IVI) of damar plant trees is 300% and the density is 582 trees/ha. The quality of copal from Kawah Ratu Resort meets SNI standards in parameters like ash content, soft point and melting point, while the saponification number is above SNI standard. Level of dung in copal chunks meet SNI standards and has better quality than copal in the form of powder. The present average income of farmers from resin tapping is Rp 624,000/person /month, which makes an average contribution of 63.08% to the total household income of farmers. But the actual economic potential of gum resin in Kawah Ratu Resort was estimated to be around Rp 596,920,000/month.